Venous Thromboembolism in Patients With Autoimmune Disorders: Findings From the RIETE Registry. (February 2020) - Sada, Pablo Ruiz; López-Núñez, Juan J.; Samperiz, Angel; Soto, María José; Pedrajas, José María; Porras, José Antonio; Peris, María Luisa; Olivé, Alejandro; Debourdeau, Philippe; Pace, Federica; Monreal, Manuel; ,
Patients with autoimmune disorders are at an increased risk of venous thromboembolism (VTE), but this association has not been consistently evaluated. We used the RIETE (Registro Informatizado Enfermedad Trombo Embólica) database to compare the rates of VTE recurrences, major bleeding, and death during the course of anticoagulation, according to the presence or absence of autoimmune disorders. Of 71 625 patients with VTE recruited in February 2018, 1800 (2.5%) had autoimmune disorders. Median duration of anticoagulant therapy was slightly longer in patients with autoimmune disorders (median, 190 vs 182 days; P = .001). On multivariable analysis, patients with autoimmune disorders had a similar risk of VTE recurrences (hazard ratio [HR]: 0.93; 95% confidence interval [CI]: 0.68-1.27) or major bleeding (HR: 1.07; 95% CI: 0.82-1.40) and a lower risk to die (HR: 0.66; 95% CI: 0.54-0.81) than those without autoimmune disorders. Patients with giant cell arteritis had the highest rates of major bleeding (8.6 events per 100 patient-years) and the lowest rate of recurrences (zero). In other subgroups, the rates of both events were more balanced. During anticoagulation, patients with or without autoimmune disorders had similar rates of VTE recurrences or major bleeding. However, there were some differences between subgroups of patients with autoimmune disorders.